Flipbook Maker Based E-Module Development Design in Thematic Learning in Elementary School - Surahman Surahman; Indri Astuti; Afandi Afandi (Universitas Majalengka, 2023)
This research is oriented towards making flipbook maker-based e-module development designs for thematic subjects at SDN 21 Riam Berasap Sukadana District, North Kayong Regency, West Borneo Province, based on the need assessment output identified by researchers empirically, namely that thematic learning has not been implemented integrated with technology products, so that in quantity there are still many students who did not meet the KKM. The research method used in this study is R&D (research and development) research, which refers to the Dick and Carey model of development design, which starts from carrying out the process of general instructional objectives to the creation of the design itself, with teachers and students being research subjects as well as recipients. benefits from the designs produced by researchers to developers who can be given special authority to carry out developments on the designs produced in this research. The design of the flipbook maker-based e-module development for thematic subjects at SDN 21 Riam Berasap was produced by taking into account the elements of an attractive appearance, language that is easy for students to understand, and the use of features in the flipbook maker application that include audiovisual elements (sounds, images, animations, and videos), which are also what students need for effective technology-based learning in the context of thematic learning in research locations.